GAMBARAN FOTO TORAKS DAN KARAKTERISTIK PASIEN ANAK UMUR 0 - 17 TAHUN DENGAN DIAGNOSIS PNEUMONIA DI RUMAH SAKIT HAJI MEDAN - CINDY AZ ZAHRA FREEMAN; EKA AIRLANGGA (JURNAL ILMIAH MAKSITEK, 2021)
Pneumonia is a cause of 800,000 deaths of children each year. Clinical examination done right is the first step in diagnosingpneumonia. Chest X-Ray is crucial in confirming the diagnosis5. If a patient has symptomps suggestive of pneumonia andthe Chest X-Ray result is consistent of pneumonia, then the diagnosis is made. To find out the characteristics and chest xrayvarieties of pneumonia patients aged 1 month to 17 years old in Haji Hospital Medan in 2017-2019. This is a descriptivestudy using the medical records from Haji Hospital Medan. From 54 medical records used, the most frequent cases arebabies aged 1 month untul 2 years old wich are 31 cases (57,4%,) compared to children and teenagers. Pneumonia isexperienced more by boys which are 32 cases (59,3%), the most frequent chest x-ray results found were right perihilarconsolidation which are 20 cases (37%), the most frequent lab result found was normal which are 14 cases (25,9%), themost frequent symptoms were fever and coughing which were 20 cases (37%). Babies have more pneumonia than childrenand teenagers, boys have pneumonia more than girls, the most frequent chest x-ray result is normal, the most frequentsymptoms are fever and coughing.